Intra- Socket Transplantation of Bicuspid to Re-establish Biologic Width - Akbar Khaiat (Shiraz University of Medical Sciences, 2019)
Transplantation and reposition of a tooth in its socket is relatively simple and predictable and can be considered as an alternative treatment option particularly in patients with financial limitation. This report describes a case of intra- alveolar transplantation of tooth #43 in a 35- year-old man. Clinical and radiographic examinations revealed tooth #43 with complicated crown-root fracture that had undergone endodontic treatment five months earlier. Reposition of mandibular bicuspid in its socket to re-establish biologic width and crown ferrule is an alternative treatment in cases with complicated crown-root fracture. Immediate replantation preserve viability of periodontal ligament cells and fibers attachment and good chance of healing is predicted.